Metabolomic alternations of follicular fluid of obese women undergoing in-vitro fertilization treatment - Song, Jingyan (Sci Rep, 2020)
Obesity exerts negative effects on the metabolic homeostasis of cells in various tissues, but how it influences ovum metabolism is not fully understood. Previous studies demonstrate that oocyte genes that regulate oxidative stress, lipid metabolism, and inflammation are highly expressed in obese women. However, the metabolic effects of these genetic variations are not clear. To address this gap, we conducted an exploratory evaluation of follicular fluid (FF) metabolites in underweight, normal-weight, overweight, and obese women undergoing in vitro fertilization (IVF) treatment. The FF samples from the underweight (Group A, n = 40), normal-weight (Group B, n = 40), overweight (Group C, n = 40), and obese women (Group D, n = 40) were analyzed using ultra-performance liquid chromatography high-resolution mass spectrometry. A novel, high-coverage, semi-targeted metabolomics method (SWATH to MRM) and a targeted metabolomics method were employed to identify and verify the differential metabolites between the four groups. Sixteen differentially expressed FF metabolites were identified. Increase of BMI was associated with upregulation of 5 metabolites, ganoderiol H, LPI (18:3), sedoheptulose 1,7-bisphosphate, austalide L and 2 - {[hydroxyl (3-hydroxy-4-methoxyphenylmethylidene] amino} acetic acid, and downregulation of 5 metabolites, 1-phenyl-1,3-elcosanedione, retinol acetate, p-Cresol sulfate, setariol and arachidonyl carnitine. These metabolites were enriched in different metabolic pathways of retinol metabolism and fatty acid metabolism. These obesity-related differential metabolites provide a pathogenesis mechanism that explains the decline of oocyte development during obesity. These results suggest that obesity affects follicular environment prior to pregnancy, a time-window that may be important for lifestyle interventions to decrease obesity levels.